Cochlear implantation and alcohol misuse. (January 2015) - Fraser, Lyndsay; Shanks, Mary; Wardrop, Peter; Allen, Agnes
<x content-type="archive" xml:space="preserve">Abstract</x> Objective To assess the outcome of patients referred to our national centre for cochlear implantation who have a history of alcohol misuse. Methods A retrospective case-note review from 1989 – current was performed. Information was collected on aetiology/duration of deafness, current alcohol habits, and co-morbidities. For those implanted, we assessed implant type, anaesthetic, and complications. Our team rated each patients' engagement with the rehabilitation programme and collected 9-month post-implant Bamford–Kowal–Bench (BKB) and 1-year post-implant categories of auditory performance (CAP) scores. Results Fourteen patients with a history of harmful drinking or alcohol dependency were identified. Aetiology of deafness was varied but most commonly included sensorineural hearing loss of unknown aetiology (7), neomycin ototoxicity (3), and head injury (2). Twelve were suitable for implantation and 11 have been successfully implanted. Three patients experienced a post-operative complication (one major/two minor). Most (eight) were rated as having good engagement with the rehabilitation process and three rated as average. Nine-month post-implant BKB scores ranged from 10 to 92 (mean 56). One-year post-implant CAP scores range from 4 to 8. Conclusion Patients with a background of alcohol misuse are being increasingly referred to our service. Alcohol is often implicated in the aetiology of deafness or can be sequelae of the psychological issues sometimes experienced by deaf patients. Even in the case of active alcohol misuse at the time of implantation, all surviving patients are currently active users and our results show that these patients can do well following implantation with the right support.